STAD STRATEGIES OF DEFENDING SELF IMAGE IN THE PUBLIC SPEAKING DELIVERED BY MR TOURISM - Afrinda, Putri Dian; Yanda, Diyan Permata (PRASASTI: Journal of Linguistics, 2019)
This article aims to explain how public speaking strategies for Mr. Tourism Sumatera Barat 2018 as a form of defending self image. The strategy that can be used is the strategy of telling Brown and Levinson about positive and negative faces. As the center of attention, a speaker must be able to maintain the face for an audience (audience) with the material presented. Public speaking training can be given in the form of material presentation and training using STAD type cooperative learning model. By using STAD type model, it is expected that the training participants can learn in their respective groups with directed instructors for the preparation of individual presentation. The results of the activities show that STAD model is effectively used to practice speech or public speaking. This is evident from the activity of the trainees following the material and confidence in public speaking.